Risk Factors of Lymph Edema in Breast Cancer Patients - Haghighat Shahpar; Akbari Atieh; Ansari Maryam; Homaei Shandiz Fatemeh; Najafi Massoome; Ebrahimi Mandana; Yunesian Masud; Mirzaei Hamid Reza; Akbari Mohammad Esmaeil (International Journal of Breast Cancer)
Background. Lymphedema secondary to breast cancer treatment is a common and serious problem for disease survivors. The objective of the current study was to identify the risk factors of secondary lymphedema after breast carcinoma treatment. Materials & Methods. The breast cancer patients who were followed up in three centers in Tehran and Mashhad in 2010 were recruited in the study. The circumference measurement was used for defining lymphedema. Results. Among 410 breast cancer patients, 123 cases (30%) developed lymphedema. Variables such as low educational level, body mass index (BMI), higher stage of disease, number of involved lymph nodes, comorbid diseases, trauma, infection, and the time after surgery showed significant correlation with the development of lymphedema. In logistic regression analysis, increase of 1 kg/m2 in BMI (OR = 1.09; 95%  CI 1.05–1.15), each number increase in lymph node involvement (OR = 1.15; 95%  CI 1.08–1.21) and the increase of every 1 month after surgery (OR = 1.01; 95%  CI 1.01–1.02) significantly increased the risk of lymphedema. Conclusion. The results of this study demonstrated that preserving a fitted BMI, emphasis on self-care, and educating preventive activities may have important roles in decreasing the lymphedema incidence and improving the patients’ quality of life.